File Under "Legacy" A Christopher Wheeldon premiere for the Royal Ballet - Shapiro, Laura (Dance Books Ltd., Alton,Hampshire (UK), 2008)
A Christopher Wheeldon premiere for the Royal Ballet. Tharp's original dancers were all willing to start from scratch and build something wildly different from anything they had ever seen or done. Male ballet dancers who are very, very talented, and have very, very open minds are Tharp's favourite clay.